2015
DOI: 10.1063/1.4931527
|View full text |Cite
|
Sign up to set email alerts
|

Understanding causes and effects of non-uniform light distributions on multi-junction solar cells: Procedures for estimating efficiency losses

Abstract: Abstract. This paper presents the mechanisms of efficiency losses that have to do with the non-uniformity of the irradiance over the multi-junction solar cells and different measurement techniques used to investigate them. To show the capabilities of the presented techniques, three different concentrators (that consist of an acrylic Fresnel lens, different SOEs and a lattice matched multi-junction cell) are evaluated. By employing these techniques is possible to answer some critical questions when designing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…By quantifying the PAR parameter, the relative losses in electrical efficiency and FF due to non-uniform illumination patterns can be evaluated. Figure 12 shows that there were no significant effects of non-uniformity or on the electrical performance of MJSCs when the PAR values were below 2 on the FF [40]. In this study, for the reflective homogeniser, the PAR values of illumination on MJSCs for the configuration design with the highest optical efficiency ranged from 1.07 to 1.14.…”
Section: Peak To Average Ratio (Par)mentioning
confidence: 64%
“…By quantifying the PAR parameter, the relative losses in electrical efficiency and FF due to non-uniform illumination patterns can be evaluated. Figure 12 shows that there were no significant effects of non-uniformity or on the electrical performance of MJSCs when the PAR values were below 2 on the FF [40]. In this study, for the reflective homogeniser, the PAR values of illumination on MJSCs for the configuration design with the highest optical efficiency ranged from 1.07 to 1.14.…”
Section: Peak To Average Ratio (Par)mentioning
confidence: 64%
“…High‐concentration PV module designs show significant performance losses due to their nonuniform flux profiles. Herrero et al reported a loss of efficiency greater than 16% for a lens‐based system with a PAR value of almost 10. The design objective is to achieve a uniform flux distribution and minimise the electrical losses due to inhomogeneous flux distribution.…”
Section: Investigated Module Conceptsmentioning
confidence: 99%
“…The resulting flux distribution on the solar cells can also be a source of electrical losses. 14,27 In this work, the distance between grid fingers for the solar cells illuminated with the flux profile at CSR 5 is optimised for highest electrical performance. The power output at grid finger distances designed for nonuniform illumination and distances designed for uniform illumination with the same total intensity is compared.…”
Section: Losses Due To the Flux Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Введение в оптическую схему вторичных оптических концентраторов (ВОК) позволяет сгладить негативные эффекты, связанные с хроматическими аберрациями и неравномерным распределением излучения по поверхности фотоэлектрических преобразователей [3,4]. Применение ВОК также обеспечивает расширение функ-циональных возможностей концентраторного модуля в части снижения требований по точности ориентации и рост его энергопроизводительности в режимах активного слежения за положением Солнца, а также способствует компенсации погрешностей взаимного расположения элементов конструкции модуля.…”
Section: Introductionunclassified